2013
DOI: 10.1007/s13312-013-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement of the Indian academy of pediatrics on integrated management of severe acute malnutrition

Abstract: An integrated management of malnutrition is likely to yield more dividends. Thus, management of SAM should constitute an important component of Integrated Management of Neonatal and Childhood Illnesses (IMNCI) program. Determination of SAM on the basis of Z-scores using WHO Growth charts is considered statistically more appropriate than cut-offs based on percentage weight deficit of the median. Considering the fact that many children with SAM can be successfully managed on outpatient basis and even in the comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…While such fi ndings may fi nd their roots in data recording at the facility level, a similar concern has also been raised by others. [14][15][16][17] The results of the study indicate that the programme was on the whole effective in ensuring relatively high levels of adherence to the follow-up visits. The study found a 24% dropout rate by the third follow-up visit, which increased to 35% for the fourth follow-up visit.…”
Section: Discussionmentioning
confidence: 86%
“…While such fi ndings may fi nd their roots in data recording at the facility level, a similar concern has also been raised by others. [14][15][16][17] The results of the study indicate that the programme was on the whole effective in ensuring relatively high levels of adherence to the follow-up visits. The study found a 24% dropout rate by the third follow-up visit, which increased to 35% for the fourth follow-up visit.…”
Section: Discussionmentioning
confidence: 86%
“…The objective was to manage severe acute malnutrition as per WHO protocol. Protocol based management (2) decreases case fatality rate of severe acute malnutrition and ensures that the child does not suffer long-term consequences on the developing brain and physical stunting. (3) A 100 admissions spanning over 5 months in the year 2014 were analysed and the results were far from the quantitative indicators set by the program.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our country does not have sufficient hospital beds for offering inpatient care to all children with SAM. Indian Academy of Paediatrics (IAP) has, therefore, recommended an integrated management of malnutrition and has advised that, management of SAM should constitute an important component of Integrated Management of Neonatal and Childhood Illnesses (IMNCI) Program (Dalwai, Choudhury et al, 2013). It has been recommended that, management of SAM should not be a standalone program but should integrate with community management of therapeutic programs, and have linkages with child treatment centre, district hospitals and tertiary level centres, offering inpatient management for SAM.…”
Section: Current Strategies For Management Of Severe Acute Malnutritionmentioning
confidence: 99%